Analysis of Field Work Practices Against Mastery of Skills and Work Readiness of Students - Sapriadi, Sapriadi; Caska, Caska; Makhdalena, Makhdalena (Journal of Educational Sciences, 2019)
This study aims to determine the effect of fieldwork experience on student skills mastery, the influence of field work experience on student work readiness, the effect of skill mastery on student work readiness, and the influence of field work experience on student work readiness through mastery of student skills. This study was conducted in YPLP SMK PGRI Bangkinang and used the entire population of 75 students who have carried out fieldwork practices. Data analysis techniques used path analysis methods. The results of this analysis indicate that field work has a positive effect on skill mastery, field work practices have a positive effect on work readiness, mastery of skills has a positive effect on work readiness, field work practices have a positive effect on job readiness through mastery of skills. Mastery of student skills and student work readiness can be improved if students' fieldwork practices are improved.